Meningkatkan Motivasi menjadi Mahasiswa yang berprestasi di Masa Pandemi - Wita Hariani; Lesi anggraini (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2022)
Achievement motivation is the driving force to achieve the highest level of learning achievement for the sake of hope for himself.Achievement motivation is influenced by two internal and external factors.The stages carried out in this activity are new students gathered in the hall, then the presenters explain the material and discuss with students at the end of the material delivery, a discussion is held on how to build students so that they excel in this pandemic.In memorizing students, it is very important that the steps to be taken are first instilled in students, don't be afraid to compete, the two students must have broad connections regardless of ethnicity, religion, class and race, the three students must have clear goals